The Development of QR Code-Based Al-Qur'an Hadith and Fiqh Textbooks for Islamic Senior High School - Khofifah, Khofifah; Mistianingrum, Silfia Putri; Aisa, Aufia (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this research is to focus on innovation in the development of QR Code-based Al-Qur'an Hadith and Fiqh textbooks that are directly accessible via YouTube links so that students become more interested in learning independently and enthusiastic about the learning process. This research uses the RnD (Research and Development) method with a 4-D development model developed by Thiagarajan (define, design, develop, disseminate). Data collection techniques in this study were observation, interviews, questionnaires, pre-test, post-test, and documentation. The data analysis technique in this study is descriptive analysis and technical analysis of the Paired Sample T-Test. Based on the results of the validation that has been carried out, the development of my mother's teaching of Al-Qur'an Hadith and Fiqh QR Code was stated to be